Design and Application of Biomedical Circuits and Systems - Yufera, Alberto; Huertas, Gloria; Calvo, Belen (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue is a collection of twelve papers on the design and application of biomedical circuits and systems. We hope you enjoy reading this Special Issue and become inspired to address technological challenges toward helping the medical industry and biologists to increase the quality of life for humans, which is the main objective. Several topics have been highlighted: muscle electrostimulation, analog front-end (AFE) circuits, waveform generators, real-time velocimetry estimators, interference suppression, bio-signal encryption, IoT electronic nose, ultrasound image processing, noise in medical imaging, elbow actuators, and aids for visually impaired people. We are conscious about the very wide scope of biomedical circuits and systems applications, and that our contribution represents only a grain of sand, though we expect to be useful in contributing to the progress of knowledge in the field.